2009
DOI: 10.1007/s00595-009-3971-3
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of postoperative hemorrhaging following a hemorrhoidectomy

Abstract: At the posterior wall, a late period hemorrhage is less likely to be found than an early period hemorrhage. It was found that the more piles that were excised, the greater the occurrence of PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 12 publications
4
15
0
Order By: Relevance
“…The procedure is simple to perform with minimal anesthesia, and is associated with very low morbidity. Pending long-term results, we (2) believe that ALTA may become the initial treatment for internal hemorrhoids, given the small number of complications to date and its minimal invasiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure is simple to perform with minimal anesthesia, and is associated with very low morbidity. Pending long-term results, we (2) believe that ALTA may become the initial treatment for internal hemorrhoids, given the small number of complications to date and its minimal invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…1 Postoperative hemorrhage is not an uncommon complication of hemorrhoidectomy. 2 Stapled hemorrhoidopexy, a novel procedure for prolapsing hemorrhoids (PPH), is thought to be an advantageous procedure for treating hemorrhoids. Data from randomized clinical trials have shown that PPH causes less pain and allows an earlier return to work than open hemorrhoidectomy.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of nine studies reported no significant difference in postoperative bleeding between patients with grades II or IV hemorrhoids who either underwent conventional hemorrhoidectomy or the LigaSure procedure [27]. A prospective study of 4880 patients who underwent the Ferguson procedure showed that male gender and surgeon variability were risk factors for DPHB [17], while other studies found that these did not impact the occurrence of DPHB [21, 31], possibly because of the small sample sizes of these studies. A prospective, randomized study of 61 patients who underwent either the Ferguson procedure or the LigaSure procedure found that although the LigaSure procedure reduced operative time and postoperative pain, there was no significant difference in postoperative bleeding between the two groups, possibly due to the slow wound healing process after the LigaSure procedure [13].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of delayed postoperative hemorrhage has been reported to be 0.9–10% [17, 18]. Some data suggest that DPHB is linked to risk factors such as the surgical procedure, infection, defecation with excessive straining, and number of piles [19–21]. Interestingly, a study that evaluated 45 patients with DPHB reported that male gender and individual surgeons were independent risk factors for DPHB [17].…”
Section: Introductionmentioning
confidence: 99%
“…Even if well performed, excision of haemorrhoids is associated with potential risks. Postoperative complications include bleeding, sometimes requiring rehospitalization and possible surgical revision for haemostasis, and severe pain lasting up to several weeks [11][12][13][14][15][16]. The use of alternative energy devices (i.e., Harmonic Scalpel Ò and LigaSure TM ), in order to minimize these risks, has been suggested.…”
Section: Discussionmentioning
confidence: 99%